Fractal Characterization and NMR Analysis of Curing-Dependent Pore Structures in Cemented Tailings Waste RockBackfill - Jianhui Qiu; Xin Xiong; Keping Zhou (Fractal and Fractional)
This study investigates the coupled effects of waste rock-to-tailings ratio (WTR) and curing temperature on the pore structure and mechanical performance of cemented tailings waste rock backfill (CTRB). Four WTRs (6:4, 7:3, 8:2, 9:1) and curing temperatures (20–50 °C) were tested. Low-field nuclear magnetic resonance (NMR) was used to characterize pore size distributions and derive fractal dimensions (<semantics>Da</semantics>, <semantics>Db</semantics>, <semantics>Dc</semantics>) at micropore, mesopore, and macropore scales. Uniaxial compressive strength (UCS) and elastic modulus (E) were also measured. The results reveal that (1) the micropore structure complexity was found to be a key indicator of structural refinement, while excessive temperature led to pore coarsening and strength reduction. <semantics>Da</semantics> = 2.01 reaches its peak at WTR = 7:3 and curing temperature = 40 °C; (2) at this condition, the UCS and E achieved 20.5 MPa and 1260 MPa, increasing by 45% and 38% over the baseline (WTR = 6:4, 20 °C); (3) when the temperature exceeded 40 °C, <semantics>Da</semantics> dropped significantly (e.g., to 1.51 at 50 °C for WTR = 7:3), indicating thermal over-curing and micropore coarsening; (4) correlation analysis showed strong negative relationships between total pore volume and mechanical strength (<semantics>R</semantics> = −0.87 for <semantics>δavs.UCS),</semantics> and a positive correlation between <semantics>Da</semantics> and UCS (R = 0.43). (5) multivariate regression models incorporating pore volume fractions, <semantics>T2</semantics> relaxation times, and fractal dimensions predicted <semantics>UCS</semantics> and E with R2 > 0.98; (6) the hierarchical sensitivity of fractal dimensions follows the order micro-, meso-, macropores. This study provides new insights into the microstructure–mechanical performance relationship in CTRB and offers a theoretical and practical basis for the design of high-performance backfill materials in deep mining environments.